2020
DOI: 10.1108/itp-01-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enterprise social media usage on task performance through perceived task structure: the moderating role of perceived team diversity

Abstract: PurposeOrganisations have widely adopted enterprise social media (ESM) to improve employees' task performance. This study aims to explore the mediating role of perceived task structure on the relationship between ESM usage and employee task performance. The authors investigate the moderating effects of perceived team diversity on the relationship between ESM usage and perceived task structure.Design/methodology/approachThe authors conducted a questionnaire survey in China on 251 working professionals who use s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 87 publications
1
57
0
Order By: Relevance
“…In recent years, more and more companies have introduced ESM internally, and the use of ESM at work has become more commonplace. Prior studies have demonstrated that the rational use of ESM can help facilitate employees' knowledge sharing [38][39][40][41], improve their work performance [3,42], and support them to build and maintain their social capital [43][44][45][46]. However, the in-depth application of ESM within organizations demands employees to use ESM extensively in their work.…”
Section: A Excessive Esm Use At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more companies have introduced ESM internally, and the use of ESM at work has become more commonplace. Prior studies have demonstrated that the rational use of ESM can help facilitate employees' knowledge sharing [38][39][40][41], improve their work performance [3,42], and support them to build and maintain their social capital [43][44][45][46]. However, the in-depth application of ESM within organizations demands employees to use ESM extensively in their work.…”
Section: A Excessive Esm Use At Workmentioning
confidence: 99%
“…Therefore, adopting the concept of affordance will help us clarify why, when, and how ESM affects individual behavior [17,18]. An important affordance enabled by ESM is communication visibility, which describes the unique visibility capabilities brought by new media technologies, such as ESM [22,42,62]. The communication visibility of ESM means that communication among employees in the workplace can be visible to a wider organizational audience [22,62,63].…”
Section: B Communication Visibility Affordancementioning
confidence: 99%
“…Specifically, the structural and cognitive dimensions positively affect job performance, whereas the relational dimension shows a negative influence. Moreover, employees' perception of task structure was found to considerably mediate the positive relationship between ESM usage and task performance (Deng et al, 2020). Cheng et al (2020) found that work engagement acts as a mediator in the positive relationship between ESM usage and employee innovative performance.…”
Section: Analysis Of Landmark Research In the Esm Literaturementioning
confidence: 97%
“…Only by doing this we can profitably explore the effect of ESM use on employee behavior and enterprise output and provide references for enterprise decision-making. Most studies investigating the purpose and dimensions of social media usage in enterprises have generally been focused on the single aspect of ESM use, and their results have shown that ESM use can contribute to task and creative performance (Ng et al , 2016; Deng et al , 2020; Sun et al , 2020a, b), organizational socialization (Leidner et al ,2018), network formation and boundary spanning (Oschand Steinfield, 2018) and team and organizational performance (Archer-Brown and Kietzmann, 2018; Cao et al , 2020). Enterprise social network use has been studied as well, and it has been found that enterprise social network use can contribute to knowledge management (Mäntymäkiand Kai, 2016; Hacker et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%